2021
DOI: 10.1002/pro.4131
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the stereospecific inhibition of the dual proline/hydroxyproline catabolic enzyme ALDH4A1 by trans‐4‐hydroxy‐L‐proline

Abstract: Aldehyde dehydrogenase 4A1 (ALDH4A1) catalyzes the final steps of both proline and hydroxyproline catabolism. It is a dual substrate enzyme that catalyzes the NAD + -dependent oxidations of L-glutamate-γ-semialdehyde to L-glutamate (proline metabolism), and 4-hydroxy-L-glutamate-γ-semialdehyde to 4-erythro-hydroxy-L-glutamate (hydroxyproline metabolism). Here we investigated the inhibition of mouse ALDH4A1 by the six stereoisomers of proline and 4-hydroxyproline using steady-state kinetics and X-ray crystallog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Multiple sequence alignment reveals that the residues related to catalytic reactions in the ALDH‐SF are highly conserved, including the catalytic residues Cys296, the proton transfer residues Arg172, Glu262 and Glu471, the cofactor coordination residues Lys186 and Glu394, and two auxiliary residues Asn163 and Gly293 (Figure 1D ). [ 24 , 25 , 26 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple sequence alignment reveals that the residues related to catalytic reactions in the ALDH‐SF are highly conserved, including the catalytic residues Cys296, the proton transfer residues Arg172, Glu262 and Glu471, the cofactor coordination residues Lys186 and Glu394, and two auxiliary residues Asn163 and Gly293 (Figure 1D ). [ 24 , 25 , 26 ]…”
Section: Resultsmentioning
confidence: 99%
“…Multiple sequence alignment reveals that the residues related to catalytic reactions in the ALDH-SF are highly conserved, including the catalytic residues Cys296, the proton transfer residues Arg172, Glu262 and Glu471, the cofactor coordination residues Lys186 and Glu394, and two auxiliary residues Asn163 and Gly293 (Figure 1D). [24][25][26] SNDH with a C-terminal His-tag was expressed in Escherichia coli and purified. SDS-PAGE analysis results showed that the molecular weight of SNDH is consistent with the theoretical size (54.4 kDa).…”
Section: Sndh Is a Member Of The Aldh Familymentioning
confidence: 99%